Lacticaseibacillus casei Strain T21 Attenuates Clostridioides difficile Infection in a Murine Model Through Reduction of Inflammation and Gut Dysbiosis With Decreased Toxin Lethality and Enhanced Mucin Production - Panpetch, Wimonrat; Phuengmaung, Pornpimol; Cheibchalard, Thanya; Somboonna, Naraporn; Leelahavanichkul, Asada; Tumwasorn, Somying (Frontiers in Microbiology, 2021)
Clostridioides difficile is a major cause of diarrhea in patients with antibiotic administration. Lacticaseibacillus casei T21, isolated from a human gastric biopsy, was tested in a murine C. difficile infection (CDI) model and colonic epithelial cells (Caco-2 and HT-29). Daily administration of L. casei T21 (1 × 108 CFU/dose) for 4 days starting at 1 day before C. difficile challenge attenuated CDI as demonstrated by a reduction in mortality rate, weight loss, diarrhea, gut leakage, gut dysbiosis, intestinal pathology changes and levels of pro-inflammatory cytokines (IL-1β, TNF-α, MIP-2 and KC) in the intestinal tissue and serum. Conditioned media from L. casei T21 exerted biological activities that fight against C. difficile as demonstrated in colonic epithelial cells by: i) suppression of gene expression and production of IL-8, an important chemokine involved in C. difficile pathogenesis, ii) reduction in expression of SLC11A1 (solute carrier family 11 member 1) and HuR (human antigen R), important genes for the lethality of C. difficile toxin B, iii) augmentation of intestinal integrity, and iv) up-regulation of MUC2, a mucosal protective gene. These results supported the therapeutic potential of L. casei T21 for CDI and the need for further study on the intervention capabilities of CDI.